2007
DOI: 10.1634/stemcells.2007-0721
|View full text |Cite
|
Sign up to set email alerts
|

The HOXB4 Homeoprotein Differentially Promotes Ex Vivo Expansion of Early Human Lymphoid Progenitors

Abstract: The HOXB4 homeoprotein is known to promote the expansion of mouse and human hematopoietic stem cells (HSCs) and progenitors of the myeloid lineages. However, the putative involvement of HOXB4 in lymphopoiesis and particularly in the expansion of early lymphoid progenitor cells has remained elusive. Based on the ability of the HOXB4 protein to passively enter hematopoietic cells, our group previously designed a long-term culture procedure of human HSCs that allows ex vivo expansion of these cells. Here, this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 38 publications
2
18
0
1
Order By: Relevance
“…We previously showed that MS-5 cells engineered to secrete HOXB4 had no phenotypic changes. 7,9 In the present study, we extended this observation to HOXC4-transduced MS-5 cells as well. This strongly argues for a direct role of the secreted homeoproteins on human HSC.…”
Section: Referencesupporting
confidence: 57%
See 2 more Smart Citations
“…We previously showed that MS-5 cells engineered to secrete HOXB4 had no phenotypic changes. 7,9 In the present study, we extended this observation to HOXC4-transduced MS-5 cells as well. This strongly argues for a direct role of the secreted homeoproteins on human HSC.…”
Section: Referencesupporting
confidence: 57%
“…Human immature hematopoietic cell isolation, labeling, culture and cloning assays were performed as already described, [7][8][9] and fully presented in the Online Supplementary Design and Methods section.…”
Section: Isolation Immuno-labeling and Cultures Of Cd34 + Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some success with murine stem and progenitor cells has been achieved, success with human stem cells has proven more elusive. In this study, we sought to take advantage of 3 previous lines of research: (1) several studies have demonstrated that overexpression of HOX4 transcription factors, and especially HOXB4, in mouse HSCs can trigger real HSC expansion, as demonstrated by competitive repopulating assays in congenic mice 1,48,49 ; (2) each of the HOX4 genes, as well as several additional genes important to HSC proliferation, are downstream transcriptional targets of NF-Ya; and (3) TAT-peptide technology offers the potential to directly deliver functional transcription factors to the nucleus of live cells. TAT-peptide technology, if it can be effectively developed, would have the dual advantages of providing a temporary effect without permanent alteration of the stem cell genome.…”
mentioning
confidence: 99%
“…Além disso, diversos estudos demonstram que a expressão dos genes HOX varia com a diferenciação das células-tronco (Giannola et al, 2000). O fator HOXB4 tem abundante expressão nas células hematopoéticas primitivas e sua expressão declina com a especificação durante o processo de diferenciação celular, isso ocorre porque o HOXB4 tem papel na regulação do balanço entre a auto-renovação e a diferenciação das células-tronco hematopoéticas, sendo responsável, principalmente, pela manutenção do fenótipo das células-tronco primitivas (Sauvageau et al, 1994;Giampaolo et al, 1994;Moretti et al, 1994;Giannola et al, 2000;Pineault et al, 2002;Haddad et al, 2008;Milson, 2009). Ainda, genes HOX apresentam funções no desenvolvimento dos linfócitos T normais, e na ativação de NK (Lawrence et al, 1996).…”
Section: Papel De Notch E Nf-kb Na Hematopoeseunclassified